Some aspects of tourism and transport in the COVID-19 pandemic time - Anna Ostrowska-Tryzno; Anna Pawlikowska-Piechotka (Jan Długosz University in Częstochowa, 2023)
This paper is aimed to describe the association between tourism and transport, seen in the perspective of the COVID-19 pandemic. The dual role of transport and tourism in the pandemic crisis is very special: it spreads the virus around the world and at the same time is mostly impacted by the pandemic negative consequences. The research was based mainly on the critical review and analysis of the secondary data (SDA method), such available resources as literature, statistic data and reports, actions taken by governments, international institutions and law regulations (published in 2020-2021). This approach allowed deep insight and overview of the most important issues of transport that have influenced tourism in the pandemic crisis. The final result of the study showed that for destinations highly dependent upon tourism-related revenue, the lockdown and transport suspension became a great concern and resulted in economy crisis. We acknowledge that due to the objective limitations, this paper cannot provide a comprehensive insight in tour- ism, transport and crisis issues. However, as this topic is a rarely discussed theme in academic texts, we hope that this paper could be found useful as it explores approaches to tourism from this new perspective. The paper ends with some reflections on sustainable development of the transport sector in the post-pandemic time, when tourism is expected to recover.